AUDIT OF LIABILITIES: THEORY, METHODOLOGY AND PRACTICE - Farxodjon Ochilov (Ustozlar uchun, 2025)
Nowadays a number of regulatory and legal documents arebeing developed on auditing and giving conclusions financial statements ofeconomic entities of various ownership types operating in the territory of theRepublic of Uzbekistan based on the requirements of international auditstandards. In this article explained the theoretical and practical considerations ofthe use of international audit standards by auditors in conducting risk-basedaudits of business entities. In addition, suggestions and recommendations weredeveloped to eliminate inconsistencies in financial statements and reduce therisk of significant misstatements.